Supergene minerals at the Huber stock and Schnod stock deposits, Krasno ore district, the Slavkovsky les area, Czech Republic - Sejkora,J.; Ondrus,P.; Fikar,M.; Veselovsky,F.; Mach,Z.; Gabasova,A.; Skoda,R.; Beran,P. (Journal of the Czech Geological Society, 2006)
This paper presents results of study of supergene minerals occuring at the Huber stock and Schnod stock in the Krasno Sn-W ore district near Horni Slavkov (Slavkovsky les area, Czech Republic). The mineralogical research is based on X-ray powder diffraction, electron microprobe analyses, optical and electron microscopy. The paper includes encyclopaedia-type presentation of the identified mineral species. The role of late hydrothermal, supergene, sub-recent and recent processes in the formation of minerals and their associations is discussed.
Keywords: Supergene minerals; mineralogy; greisen; Huber stock; Schnod stock; Krasno near Horni Slavkov; Slavkovsky les area; western Bohemia; Czech Republic